The impact of dysphagia on quality of life in stroke patients - Kim, Doo-Young; Park, Hyo-Sik; Park, Si-Woon; Kim, Jae-Hyung (Medicine (Baltimore), 2020)
The objective of this study was to investigate the quality of life in stroke patients using a swallowing quality of life (SWAL-QOL) questionnaire. The correlation between SWAL-QOL questionnaire outcome and videofluoroscopic dysphagia scale (VDS) scores in stroke patients was also determined.This cross-sectional study was retrospectively conducted with 75 stroke patients with dysphagia symptoms. Videofluoroscopic swallowing study (VFSS) and SWAL-QOL questionnaires were performed for all patients. These patients were divided into an oral feeding group and a tube feeding group. SWAL-QOL scores were compared between the 2 groups. The severity of dysphagia was estimated by VDS scores according to the videofluoroscopic swallowing study results. The relationships between SWAL-QOL scores and VDS scores were also investigated.The composite score was 48.82 ± 19.51 for the tube feeding group and 53.17 ± 25.42 for the oral feeding group. There were significant differences in burden and sleep subdomains of the SWAL-QOL between the 2 groups (P = .005 and P = .012, respectively). There was a significant negative correlation between the composite score of SWAL-QOL outcome and the total VDS score (r = -0.468, P = .012). The pharyngeal-phase score of the VDS had significant negative correlations with the SWAL-QOL subdomains of burden (r = -0.327, P = .013), mental health (r = -0.348, P = .008), and social functioning (r = -0.365, P = .029).To improve the quality of life of stroke patients, dysphagia rehabilitation should focus on the pharyngeal phase of dysphagia.